Effect of Nutritional Status on Infants (0-1 Years) on Growth - anggoro, sarni (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2022)
The stage of growth and development really requires good nutritional intake. Even though the stunting rate in Indonesia is decreasing. This research is quantitative with a cross sectional approach. The population of this research is mothers who have babies regarding the nutritional status of infants (0-1 years) totaling 74 people in January 2022 at Sewon I Health Center Work Area, Bantul. Sampling using total sampling. Data collection techniques through observation. The data collection instrument was the KMS book, weight scales and body length measurements. Bivariate analysis in this study using the Kendall Tau test. The results of the analysis can be concluded that obtained from this study there are 4 children (5.4%) in the category of poor nutrition, 61 children (82.4%) with good nutritional status and 9 children (12.2%) more nutritional status. There are data as many as 65 children (87.8%) in the category of normal growth and development. From the correlation results, there is the effect of nutritional status in infants (0-1 years) on growth and development, which is indicated by a significance value which is 0.000. This shows that there is a significant effect, between the influence of nutritional status on growth and development.